The Punishment and Dicipline of Ahmadi Women: A Case Study In Transito Dormitory In Mataram - Abdul Gaffar (HUMANISMA : Journal of Gender Studies, 2022)
Indonesian Ahmadiyya community (Jamaah Ahmadiyah Indonesia (JAI)) in Lombok has taken refuge in Transito Dormitory in Mataram since 2006. Therefore, it is interesting to see how Ahmadi women experienced expulsion and fled to Transito Dormitory due to the differences in Ahmadiyya beliefs regarding Mirza Ghulam Ahmad as a prophet. This study aimed to observe the punishment and discipline they endured during expulsion and refuge in Transito Dormitory. This study used a qualitative method with a phenomenological approach and Michael Foucault's theory of punish and discipline. The results of this study revealed that Ahmadi women who took refuge in Transito Dormitory had difficulties in carrying out family functions. They had difficulties in managing all the household needs with limited facility. They were lack of water for cooking, washing, and other needs. This paper also showed that Ahmadi women who took refuge in Transito Dormitory experienced punishment and discipline through limited access and strict control mechanisms that forced them not to leave Transito Dormitory in MataramJamaah Ahmadiyah Indonesia Lombok telah mengungsi di Asrama Transito Mataram sejak tahun 2006. Oleh karena itu, menarik untuk dilihat bagaimana perempuan Ahmadiyah mengalami pengusiran hingga mengungsi di Asrama Transito Mataram karena perbedaan keyakinan Jamaah Ahmadiyah Indonesia mengenai Mirza Ghulam Ahmad sebagai nabi. Penelitian ini bertujuan untuk melihat penghukuman dan pendisiplinan yang mereka alami selama mengalami pengusiran dan pengalaman mengungsi di Asrama Transito. Penelitian ini menggunakan metode kualitatif dengan pendekatan fenomenologi dan teori penghukuman dan pendisiplinan Michael Foucault. Hasil penelitian ini mengungkapkan bahwa perempuan Ahmadiyah yang mengungsi di Asrama Transito mengalami kesulitan dalam menjalankan fungsi-fungsi keluarga, kesulitan dalam mengelola semua kebutuhan rumah tangga dengan fasilitas yang terbatas. Kekurangan air untuk memasak, mencuci dan kebutuhan lain. Tulisan ini juga menunjukkan bahwa Perempuan Ahmadiyah yang mengungsi di Asrama Transito mengalami penghukuman dan pendisiplinan melalui akses-akses yang serba terbatas serta mekanisme kontrol yang ketat yang memaksa mereka tidak bisa keluar dari Asrama Transito Mataram.